DESENVOLVIMENTO DE UM SISTEMA DE TELEMETRIA PARA MONITORAMENTO TÉRMICO EM CASAS DE VEGETAÇÃO - Barbosa, R. Z.; Perea Martins, J. E. M. (Revista Brasileira de Engenharia de Biossistemas, 2014)
This paper shows the design of a telemetry system used for greenhouse temperature monitoring, which includes hardware and software aspects. The temperature data is transmitted by radio to a computer that has software specially designed in this work, which performs the data reception and storage into a the text file format that enables the later data processing for other software as text editors or spreadsheets. The telemetry hardware was based on a radio communication module that has a specific pin to configure it as transmitter or receiver, what make easier the hardware design. The results show a radio transmission range at 120 meters, without errors. The telemetry system developed can be connected to any sensing device that has a serial communication interface with RS-232 standard, which is common in commercial measuring instruments and enable the system usage for other physical parameters measurement in the agricultural and environmental areas.